Innovation-Driven Supply Chain Optimization: Balancing Efficiency and Sustainability - Nurhaliza Nurhaliza (Politeknik Siber Cerdika Internasional, 2024)
This study explores how innovation-driven supply chain optimization can balance efficiency and sustainability across manufacturing and retail sectors. Using a mixed-methods approach, data were collected from 50 companies that have integrated practices such as IoT, data analytics, and circular economy models. The results indicate that these innovative practices significantly enhance both efficiency and sustainability. Specifically, companies implementing digital technologies reported improved lead times and resource management, while sustainable sourcing contributed to a reduction in carbon footprint. However, challenges such as high initial costs and integration with existing systems were noted. These findings support theories of sustainable development and resource-based views, suggesting that innovation-driven practices can enable organizations to achieve both operational and environmental objectives. Practical implications highlight the need for phased technology adoption and collaboration with stakeholders to overcome implementation barriers. Future research could investigate the long-term effects of emerging technologies, such as AI and blockchain, on sustainable supply chains in additional sectors.